Victorian Jews Through British Eyes. - Cowen, Anne (Littman Library of Jewish Civilization., 1986)
This book reproduces, with commentary, pictures from Victorian illustrated magazines such as 'Punch', 'The Illustrated London News', and 'The Graphic', to show how Jewish subjects were presented to Victorian readers.